2019
DOI: 10.12669/pjms.35.6.165
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, diagnosis and management of locally advanced breast cancer: Is it different in low/middle income countries?

Abstract: Background and Objective:Breast cancer incidence is increasing and it is highest in low income countries. The main challenge is regarding awareness, screening, late presentation and its management in a third-world country. Our objective was to share the experience faced in various presentations, diagnosis and management of locally advanced breast cancer (LABC) in a third world country and discuss if they are different with respect to developed countries.Methods:It is a retrospective case series study performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…12 Manzoor S et al also highlighted importance of awareness and patient education to improve the delayed presentation. 18 We observed that benign breast diseases are also perceived as stigma and cause negative connotations and delay in seeking appropriate medical care leading to their progression. Young unmarried females considered it difficult to find husband and getting married, if the disease is disclosed.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 84%
See 1 more Smart Citation
“…12 Manzoor S et al also highlighted importance of awareness and patient education to improve the delayed presentation. 18 We observed that benign breast diseases are also perceived as stigma and cause negative connotations and delay in seeking appropriate medical care leading to their progression. Young unmarried females considered it difficult to find husband and getting married, if the disease is disclosed.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 84%
“… 12 Manzoor S et al also highlighted importance of awareness and patient education to improve the delayed presentation. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Some women may be aware of a palpable finding but have no easy access to treatment or be ignorant of its significance. The lack of screening and resources means that patients are diagnosed with advanced disease the majority of the time 1,6,47 . In addition, in many cases, social stigma related to cancer results in delays in diagnosis and lack of funding/advocacy toward cancer related interventions 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of screening and resources means that patients are diagnosed with advanced disease the majority of the time. 1,6,47 In addition, in many cases, social stigma related to cancer results in delays in diagnosis and lack of funding/advocacy toward cancer related interventions. 48,49 A VSI protocol for palpable breast abnormalities helps to address many of these obstacles (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer in females, accounting for 31.8% of all cancers [ 1 ]. Its incidence is increasing, particularly in low socioeconomic groups [ 2 ]. Breast cancer is common above the age of 40 years, and it is the commonest between 41 and 50 years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%